PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT (CRM) TERHADAP CUSTOMER SATISFACTION DAN CUSTOMER LOYALTY PADA PELANGGAN MATAHARI DEPARTMENT STORE - Meyske Ham (Jurnal Strategi Pemasaran, 2016)
This study was conducted to determine the effect Benefits of Customer Relationship Management and Customer satisfation to Customer Loyalty in Customers Matahari Department Store. Customer relationship management (CRM) is part of a marketing strategy to get satisfaction and increase customer loyalty. CRM and customer satisfaction can encourage customer loyalty where customers do not easily switch to other companies. The population is all customers Matahari Department Store, and the sample are customers of at least 2 times shopping at Matahari Department Store and have the customer's card or MCC were selected by purposive sampling and analytical techniques used is Partial Least Square (PLS) and the Statistical product and Service Solutions (SPSS). The research proves that CRM has a positive effect on customer loyalty and customer satisfaction has positive influence on loyalty. Customer satisfaction does not affect the relationship CRM to customer loyalty.